2014
DOI: 10.3171/2014.7.focus14318
|View full text |Cite
|
Sign up to set email alerts
|

Fully endoscopic microvascular decompression for trigeminal neuralgia: technique review and early outcomes

Abstract: Object Fully endoscopicmicrovascular decompression (E-MVD) of the trigeminal nerve was initially described more than 1 decade ago, but has not yet gained wide acceptance. The authors present the experience of their first 47 consecutive E-MVDs for trigeminal neuralgia (TN). Methods All surgeries were performed by a single surgeon (J.Y.K.L.) at the Pennsylvania Hospital at the University of Pennsylvania. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 26 publications
2
42
1
2
Order By: Relevance
“…The authors recently published their early experience with fully e-MVD for trigeminal neuralgia with promising results. 9 In this series of 47 consecutive patients undergoing E-MVD, there was again no morbidity attributable to using the endoscope, and patient outcomes were promising with 94% of patients endorsing improvement of preoperative symptoms. The authors are currently preparing a manuscript comparing results between E-MVD and conventional MVD, and identification of vessels is more successful with the use of the endoscope; however, early results demonstrate equivalent pain-free results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The authors recently published their early experience with fully e-MVD for trigeminal neuralgia with promising results. 9 In this series of 47 consecutive patients undergoing E-MVD, there was again no morbidity attributable to using the endoscope, and patient outcomes were promising with 94% of patients endorsing improvement of preoperative symptoms. The authors are currently preparing a manuscript comparing results between E-MVD and conventional MVD, and identification of vessels is more successful with the use of the endoscope; however, early results demonstrate equivalent pain-free results.…”
Section: Discussionmentioning
confidence: 92%
“…[5][6][7][8] More recently, endoscopic approaches have been developed for use in lateral skull-base surgery, and in particular, in the surgical treatment of trigeminal neuralgia. [9][10][11] In this article, the fully endoscopic microvascular decompression (E-MVD) for patients with trigeminal neuralgia is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence is about 20-30% in most of the published series of MVD. 1,2,13,14 In Barker and Jannetta's series of 1185 cases recurrence rate was 30% in 20 years followed up period and most of the recurrence occurred within fi rst two years after surgery. 1 Burchiel et al reported 6% recurrence at 60 months and 42% in 100 months.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, visualization of neurovascular conflict may be difficult intraoperatively, particularly in the setting of distal compression near the porus trigeminus, when a prominent bony ridge along the posterior wall of the petrous temporal bone obscures visualization of CN V, or when the offending vessel is small and located medial and parallel to the nerve. [18][19][20] Preoperative imaging in those cases may help in surgical planning, for instance, by suggesting the use of an endoscope as an adjunct to the standard operating microscope. 18,19 Recently, DTI has been used to better understand microstructural tissue changes of the trigeminal root in patients with unilateral TGN.…”
Section: Imaging Of Neurovascular Contactmentioning
confidence: 99%